A production method of a hard carbon negative electrode material
Patent Information
- Application Number
- CN202511385956.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-26
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-26
AI Technical Summary
[0004]本发明要解决的技术问题是:现有技术中存在高温碳化能耗高损性能,效率低难控稳定的缺点,为此我们提出一种硬碳负极材料的生产方法
[0025] In this invention, microwave plasma low-temperature carbonization technology is employed to precisely stabilize the electron temperature within the 2-3 eV range. High-energy particles within this range efficiently break the CH and CO bonds in biomass, while avoiding excessive local graphitization and pore collapse caused by excessively high energies. Combined with deep vacuum drying under 1-3 kPa absolute pressure during the raw material pretreatment stage, the oxidation and erosion of the carbon skeleton by water and oxygen impurities are prevented. Subsequent low-temperature annealing at 300℃ eliminates internal stress and stabilizes the carbon structure. In-situ doping can also introduce active sites. This process combination significantly reduces energy consumption during carbonization, effectively protects the natural microporous template of the biomass raw material, and forms an ideal pore size distribution of 1-10 nm and a suitable interlayer spacing of 0.36-0.40 nm. This results in an initial coulombic efficiency of over 85% for the hard carbon anode material, with a capacity retention rate exceeding 90% after 2000 cycles at 1C rate. This significantly improves the problems of decreased specific surface area and uneven pore size caused by traditional high-temperature processes, greatly enhancing the electrochemical performance of the material.
Smart Images

Figure CN121180973B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of anode material technology, and in particular to a method for producing a hard carbon anode material. Background Technology
[0002] In the field of hard carbon material preparation, traditional methods mainly rely on high-temperature thermal carbonization processes. This technology typically uses biomass precursors or organic polymers as raw materials, and achieves carbonization through prolonged high-temperature heat treatment under an inert atmosphere. Based on the principles of heat conduction and radiation heating, it requires equipment such as large resistance furnaces or rotary kilns to gradually transfer heat energy to the interior of the material through an external heat source, causing the organic components to undergo pyrolysis reactions and form sp2 hybrid carbon structures. During this process, the material gradually forms a graphite-like microcrystalline structure with short-range order and long-range disorder, as well as abundant nanopores. These characteristics make it particularly suitable for energy storage fields such as lithium-ion battery anodes.
[0003] The aforementioned and existing related technologies often suffer from the following drawbacks: The high-temperature thermal carbonization process has two significant problems: First, due to the extremely high carbonization temperature, the production process consumes a huge amount of energy, and the high-temperature environment easily causes localized over-graphitization or pore structure collapse in hard carbon materials, resulting in uneven pore size distribution and a decrease in specific surface area, which in turn affects electrochemical performance; Second, traditional processes rely on slow heat conduction, which not only results in low carbonization efficiency and long production cycles, but also causes temperature field distribution fluctuations in batch production, making it difficult to effectively control the consistency of material structure and batch stability. Summary of the Invention
[0004] The technical problem to be solved by this invention is that the existing technology has the disadvantages of high energy consumption, high performance loss, low efficiency and difficulty in controlling stability during high-temperature carbonization. To address this, we propose a method for producing hard carbon anode materials.
[0005] To achieve the above objectives, this application adopts the following technical solution: a method for producing hard carbon anode material, comprising the following steps:
[0006] S1. The biomass raw material is crushed, graded and deeply dried to obtain a dry powder with a particle size of less than 100μm and a moisture content of less than 2wt%.
[0007] S2. In a low-pressure inert atmosphere, a working gas is introduced into the reaction chamber, and microwave energy is applied to generate plasma. The dried powder is continuously and uniformly fed into the plasma region for carbonization reaction. The plasma state is monitored in real time by optical emission spectrum, and the electron temperature of the plasma is stably controlled within the range of 2-3 eV by adjusting the microwave power or working gas pressure, while the reaction temperature of the material bed is controlled within 150-200℃.
[0008] S3. The carbonized material is subjected to annealing stabilization and passivation treatment to obtain the hard carbon material.
[0009] Furthermore, in S2, the plasma state is monitored in real time using optical emission spectroscopy, and the electron temperature of the plasma is stably controlled within the range of 2-3 eV by adjusting the microwave power or working gas pressure. Specifically, the following operations are performed:
[0010] S21. Install an optical emission spectroscopy probe on the plasma reaction chamber to focus on monitoring the argon atom spectral lines and the second positive band of nitrogen molecules;
[0011] S22. Pre-calibrate the argon atomic spectral line intensity under the current process gas background. Compared with the intensity of the second positive band of nitrogen molecules ratio The corresponding functional relationship curve between the plasma electron temperature and the plasma electron temperature is obtained, and the target intensity ratio range corresponding to the target electron temperature of 2-3 eV is determined from the functional relationship curve, and this range is set as the benchmark for process control.
[0012] S23. Introduce working gas, adjust the pressure in the reaction chamber to the target value, apply microwave power, minimize reflected power through the three-screw tuner, and successfully ignite and form a stable plasma.
[0013] S24. The optical emission spectroscopy probe acquires the emission spectrum of the plasma in real time and calculates it in real time. The instantaneous ratio;
[0014] S25. Compare the real-time ratio with the target ratio range. If the real-time ratio is lower than the lower limit of the target range, increase the microwave power or decrease the reaction chamber pressure appropriately. If the real-time ratio is higher than the upper limit of the target range, decrease the microwave power or increase the reaction chamber pressure appropriately. If the real-time ratio is within the target range, keep the existing parameters unchanged.
[0015] S26. After executing the parameter adjustment command, return to S24, collect spectral data again and calculate the ratio to form a continuous closed-loop control loop, ensuring that the electron temperature is dynamically stable within the ideal range of 2-3 eV.
[0016] Furthermore, the working gas in S2 is argon, and the pressure inside the reaction chamber is stabilized in the range of 10-100 Pa.
[0017] Furthermore, the power of the microwave energy mentioned in S2 is 500-1100W.
[0018] Furthermore, in S2, the electron temperature of the plasma is set to 2.5 eV.
[0019] Furthermore, in S2, during the carbonization reaction, a doping source gas, which is ammonia or phosphorus-containing aerosol, is introduced into the reaction chamber to achieve in-situ doping of nitrogen or phosphorus into the hard carbon material.
[0020] Furthermore, the deep drying described in S1 is carried out in a vacuum environment at a temperature of 80-120°C for no less than 12 hours, and the absolute pressure of the vacuum environment is 0.5-3.5 kPa.
[0021] Furthermore, the absolute pressure of the vacuum environment is 1-3 kPa.
[0022] Furthermore, the specific conditions for the annealing stabilization treatment described in S3 are as follows: under an inert atmosphere, the temperature is increased to 300-400℃ at a heating rate of 1-10℃ / min, and held for 1-10 minutes.
[0023] Furthermore, it also includes step S4, which involves airflow pulverization and classification of the passivated material to screen out particles with a D50 particle size of 8-15μm as the final hard carbon anode material.
[0024] The technical effects and advantages of this invention are as follows:
[0025] In this invention, microwave plasma low-temperature carbonization technology is employed to precisely stabilize the electron temperature within the 2-3 eV range. High-energy particles within this range efficiently break the CH and CO bonds in biomass, while avoiding excessive local graphitization and pore collapse caused by excessively high energies. Combined with deep vacuum drying under 1-3 kPa absolute pressure during the raw material pretreatment stage, the oxidation and erosion of the carbon skeleton by water and oxygen impurities are prevented. Subsequent low-temperature annealing at 300℃ eliminates internal stress and stabilizes the carbon structure. In-situ doping can also introduce active sites. This process combination significantly reduces energy consumption during carbonization, effectively protects the natural microporous template of the biomass raw material, and forms an ideal pore size distribution of 1-10 nm and a suitable interlayer spacing of 0.36-0.40 nm. This results in an initial coulombic efficiency of over 85% for the hard carbon anode material, with a capacity retention rate exceeding 90% after 2000 cycles at 1C rate. This significantly improves the problems of decreased specific surface area and uneven pore size caused by traditional high-temperature processes, greatly enhancing the electrochemical performance of the material. Attached Figure Description
[0026] The disclosure of this invention is illustrated with reference to the accompanying drawings. It should be understood that the drawings are for illustrative purposes only and are not intended to limit the scope of protection of this invention. In the drawings, the same reference numerals are used to refer to the same parts:
[0027] Figure 1 This is a flowchart of the present invention. Detailed Implementation
[0028] It is readily understood that, based on the technical solution of this invention, those skilled in the art can propose various interchangeable structural methods and implementations without altering the essential spirit of the invention. Therefore, the following detailed embodiments and accompanying drawings are merely illustrative examples of the technical solution of this invention and should not be considered as the entirety of the invention or as limitations or restrictions on the technical solution of this invention.
[0029] Reference Figure 1 As shown, the present invention provides a technical solution: a method for producing a hard carbon anode material, comprising the following steps:
[0030] Step 1: Raw material pretreatment and preparation
[0031] First, select biomass raw materials rich in lignocellulose and with a dense structure, such as teak chips, walnut shells, and coconut shells. These raw materials possess abundant natural microporous structures, serving as templates for forming ideal hard carbon structures. Use a jaw crusher or hammer crusher to crush the raw materials into coarse particles with a diameter of less than 5mm to facilitate subsequent fine grinding.
[0032] The coarsely crushed material is then fed into a planetary ball mill or air jet mill under inert gas protection for ultrafine grinding. The preferred inert gas is N2. The ball mill parameters are set as follows: rotation speed 350-450 rpm, zirconium oxide grinding balls to material mass ratio 10:1, and grinding time 4-6 hours. During grinding, the mechanical force also activates the cellulose microcrystalline structure, which is beneficial for subsequent carbonization. After grinding, the material is classified using an ultrasonic vibrating sieve to obtain powder with a particle size less than 100 μm.
[0033] Finally, the graded fine powder is transferred to a vacuum drying oven. Unlike existing technologies, the drying parameters of the vacuum drying oven are set as follows: temperature 80-100℃, absolute pressure 0.5-3.5kPa, with the optimal range being 1-3kPa, and the drying time is no less than 12 hours. This is because any residual moisture will vaporize in the subsequent vacuum plasma environment, which will damage the process stability and may introduce oxygen impurities. After drying, a rapid moisture analyzer must be used immediately to ensure that the moisture content is strictly controlled within 2% by weight. The material that meets the standard should be quickly transferred to a sealed glove box filled with argon for temporary storage to prevent moisture absorption and oxidation.
[0034] Furthermore, depending on the actual needs, if in-situ doping is required, then dopant needs to be prepared. For example, if nitrogen doping is planned, high-purity ammonia gas needs to be prepared; if phosphorus doping is planned, triethyl phosphate and ethanol need to be mixed into a solution at a volume ratio of 1:9 and then made into an aerosol state that can be carried by a carrier gas using an ultrasonic atomizer.
[0035] Step 2: Microwave plasma low-temperature carbonization and in-situ functionalization
[0036] First, close the reaction chamber and start the vacuum unit. Preferably, the vacuum unit is a combination of a molecular pump and a mechanical pump. Evacuate the chamber to below 5.0 × 10⁻³ Pa, close the valves, and let it stand for 30 minutes. Confirm that the vacuum change rate is <5 Pa / min to ensure good system airtightness. Check whether the cooling water circulation of the microwave system, including the microwave generator, circulator, water load, and three-screw mixer, is normal.
[0037] Then, approximately 200g of dried raw material powder is loaded into the dedicated powder feeder on the reaction chamber through the glove box. A star-shaped feeder is preferred. All valves are closed, and the reaction chamber is evacuated back to a basic vacuum. A working gas, preferably argon, is then slowly introduced into the chamber through a mass flow controller to precisely stabilize the pressure within the reaction chamber at 10-100 Pa. The low-speed rotation device of the sample stage is then activated to ensure that the powder bed is uniformly exposed to the plasma.
[0038] Next, set the microwave power to 500-1100W and slowly adjust the three-screw tuner to the minimum reflection power. At this point, a bright argon plasma sphere can be observed forming above the sample stage. Immediately activate the optical emission spectroscopy probe to monitor the plasma emission spectrum in real time.
[0039] It should be added that the intensity of the ArI line should be closely monitored to control the plasma density. The electron temperature should be estimated by comparing the intensity of the ArI line with that of the second positive band of N2 and stabilized in the range of 2-3 eV. Stabilization can be achieved by fine-tuning the microwave power or the working gas pressure.
[0040] Specifically, in microwave plasma carbonization, real-time monitoring and stable control of the plasma state are crucial to ensuring consistent material properties. Monitoring the intensity of the ArI spectral line is important because this line originates from the excitation of argon atoms, and its intensity is directly related to the density of high-energy electrons. Therefore, it can serve as a reliable indicator of plasma density. Stable density ensures a constant concentration of active particles, thereby enabling the carbonization reaction to proceed uniformly.
[0041] Furthermore, the electron temperature can be estimated by comparing the intensities of the ArI line and the second positive band of N2. The principle is that the intensity of atomic spectral lines is relatively insensitive to electron temperature, while the intensity of nitrogen molecule spectral bands is very sensitive to it. The ratio of their intensities has a functional relationship with the electron temperature; therefore, the average electron temperature of the system can be deduced by calculating this ratio.
[0042] Maintaining the electron temperature within 2-3 eV is crucial. This energy range is sufficient to efficiently break the CH and CO bonds in biomass, initiating the carbonization reaction, while avoiding structural damage such as excessive graphitization or pore collapse caused by excessive energy. A rapid response can be achieved by fine-tuning the microwave power or operating pressure; increasing the power or decreasing the pressure will increase the electron temperature and density, and vice versa, thus enabling precise closed-loop control of the parameters.
[0043] Furthermore, the plasma state is monitored in real time using optical emission spectra, and the electron temperature of the plasma is stably controlled within the range of 2-3 eV by adjusting microwave power or working gas pressure. Specifically, the following operations are performed:
[0044] 21: Install an optical emission spectroscopy probe on the microwave plasma reaction cavity and calibrate it to ensure it is aligned with the plasma luminescence region, enabling it to accurately identify and acquire intensity signals of specific wavelength spectral lines. Focus on monitoring:
[0045] Argon atomic spectral line (ArI): The spectral line at 750.4 nm was selected as the monitoring target.
[0046] The second positive band of nitrogen molecules (N2SPS): Select a specific wavelength range, such as the band generated by the C³Πu→B³Πg transition.
[0047] 22: The intensity of the ArI spectral line under the current process gas background is pre-calibrated through experiments or theoretical calculations. With N2 spectral intensity ratio The curve showing the functional relationship between plasma electron temperature and plasma electron temperature.
[0048] The target intensity ratio range corresponding to the target electron temperature of 2-3 eV is determined from the function relationship curve, and this range is set as the reference for adjustment and control.
[0049] 23: Introduce working gas, adjust the pressure in the reaction chamber to the target value, apply microwave power, minimize reflected power using the three-screw tuner, and successfully ignite and form a stable plasma.
[0050] 24: The optical emission spectroscopy probe begins to acquire the emission spectrum of the plasma in real time and calculates it in real time. The instantaneous ratio.
[0051] 25: Compare the calculated real-time ratio with the target ratio range. If the real-time ratio is lower than the lower limit of the target range, it indicates that the electron temperature is too low. The control system issues an instruction to appropriately increase the microwave power or appropriately decrease the reaction chamber pressure. If the real-time ratio is higher than the upper limit of the target range, it indicates that the electron temperature is too high. The control system issues an instruction to appropriately decrease the microwave power or appropriately increase the reaction chamber pressure. If the real-time ratio is within the target range, the existing parameters remain unchanged.
[0052] After executing the above parameter adjustment instructions, return to 34, collect spectral data again and calculate the ratio to form a continuous closed-loop control loop, ensuring that the electron temperature is dynamically stable within the ideal range of 2-3 eV.
[0053] Furthermore, it should be added that the above steps need to be continuously run throughout the carbonization reaction process to counteract changes in the plasma state that may be caused by feeding, material reaction, or slight fluctuations in the system.
[0054] Furthermore, it should be added that after the powder feeder is turned on, the biomass powder is uniformly fed into the plasma region at a rate of 10 g / min. The powder is instantly surrounded by high-energy electrons and active particles, and the CH and CO bonds on its surface are rapidly broken, resulting in dehydrogenation and deoxygenation reactions, releasing small molecule gases such as H2, CO, and CH4, which are continuously removed by the vacuum pump unit. This process is a strongly exothermic reaction, requiring monitoring of the bed temperature using an infrared thermal imager and strict control within a core window of 180±20℃ using a cooling system. The residence time of the material in the reaction zone is controlled to approximately 15 minutes by adjusting the feed rate and bed thickness.
[0055] Furthermore, it should be added that if doping is required, when the carbonization process reaches the 5th minute and the plasma state is most stable, ammonia gas should be introduced through another MFC, with the flow rate set to 5% of the total argon flow rate, or the atomizer should be turned on to bring the phosphorus source aerosol into the reaction chamber via the carrier gas (Ar). Active nitrogen or phosphorus species will directly embed into the growing carbon framework, forming active sites such as pyridine nitrogen, graphitic nitrogen, or CP bonds.
[0056] 26: The carbonized material is discharged from the bottom of the reaction chamber and falls into a collection tank connected to the vacuum lock. Throughout the process, the reaction chamber is maintained in a vacuum and plasma state, enabling continuous feeding and discharging.
[0057] Step 3: Post-processing and structural stabilization
[0058] 31: The collected carbide powder is transferred to a tube furnace and heated to 300°C at a rate of 10°C / min under continuous high-purity argon protection, and held at that temperature for 5 minutes. This low-temperature annealing process can eliminate the internal stress of the material, promote the bonding of some dangling bonds, and make the carbon skeleton structure more stable, while not causing significant graphitization or pore collapse. Afterwards, it is naturally cooled to below 50°C.
[0059] 32: After annealing, the material continues to cool to room temperature in the furnace under argon protection. Before exiting the furnace, a passivation treatment must be performed with extreme care: a low-oxygen mixture (such as Ar containing 2% O2) is introduced into the furnace tube at an extremely slow rate, causing slight oxidation on the material surface to form a very thin passivation film. This prevents the material from undergoing severe oxidation or spontaneous combustion when subsequently exposed to air, ensuring production safety.
[0060] Step 4: Finished Product Processing and Quality Control
[0061] 41: The passivated material is lightly ground using a high-efficiency air jet mill, primarily to break up any soft agglomerates that may form during the process. Then, a precision air classifier is used to rigorously screen particles with a particle size distribution (D50) between 8 and 15 μm. Powders that are too fine have an excessively large surface area, leading to a decrease in initial efficiency; particles that are too coarse affect lithium-ion / sodium-ion diffusion kinetics. Qualified particles are collected, while unqualified particles may be returned to step three or treated as substandard products, depending on the circumstances.
[0062] 42: Conduct comprehensive characterization of samples from each batch of products, as detailed below:
[0063] Physical properties: Particle size distribution was detected using a laser particle size analyzer; specific surface area and pore size distribution were determined using the BET nitrogen adsorption method; interlayer spacing was calculated using X-ray diffraction analysis, and the acceptable range should be 0.36-0.40 nm.
[0064] Chemical properties: X-ray photoelectron spectroscopy was used to analyze the surface elemental composition and functional group types (such as CC, CO, N- / P- doping types, etc.).
[0065] Electrochemical performance: The cells were fabricated as CR2032 button cells for testing. Key performance indicators included: initial coulombic efficiency, reversible capacity, and cycle performance (capacity retention >90% after 2000 cycles at 1C rate).
[0066] 43: Products that pass quality inspection are vacuum-packed in an aluminum foil bag in a glove box environment and filled with argon gas. The outer packaging should indicate the product batch number, weight, and key specifications. Store in a dry, cool place.
[0067] Furthermore, based on the deep drying process described in step one above, it's important to note that extremely low moisture content is crucial for maintaining the stability of the microwave plasma environment. If moisture remains, it will instantly vaporize in the vacuum chamber, generating a large amount of steam, drastically altering the chamber pressure and gas composition, leading to plasma impedance mismatch, a sharp increase in microwave reflection power, and even discharge shutdown. Strict moisture control avoids these process fluctuations, ensuring stable coupling of plasma energy to the reaction system, guaranteeing the continuity and consistency of the carbonization reaction. Deep drying fundamentally eliminates the negative impact of water and oxygen impurities on the carbonization process and material properties. Water molecules decompose into hydroxyl radicals in high-temperature plasma. These reactive species oxidize and erode the forming carbon skeleton, introducing defect sites and potentially generating oxygen-containing functional groups on the surface, reducing the material's conductivity and initial coulombic efficiency. Therefore, pre-treatment deep drying is a key guarantee for obtaining structurally intact and high-performance hard carbon anodes.
[0068] Example 1: Based on the above-mentioned deep drying supplement, the absolute pressure of 1-3 kPa in the deep drying in step 1 above is set to an absolute pressure of 2 kPa, while other contents remain unchanged;
[0069] Under vacuum drying conditions with an absolute pressure of 2 kPa, the boiling point of water is significantly reduced to approximately 60°C. This allows for the efficient removal of bound and free water from biomass feedstocks at a relatively low temperature of 80-100°C. This gentle drying method avoids damage to the microstructure of heat-sensitive biomass caused by high temperatures, protecting its natural template pores as a hard carbon precursor. Simultaneously, it strictly controls the moisture content to below 2%, laying a solid foundation for subsequent processes.
[0070] Example 2: Based on the above-mentioned deep drying supplement, the absolute pressure of 1-3 kPa in the deep drying in step one above is set to an absolute pressure of 1 kPa, while other contents remain unchanged;
[0071] Under a deep vacuum environment with an absolute pressure of 1 kPa, the boiling point of water drops sharply to approximately 45.8°C, which provides extremely high dehydration driving force for biomass feedstocks at drying temperatures of 80-100°C. Moisture is rapidly and completely evaporated and removed. This ultra-low moisture content (controllable to within 1.5%) provides a stable and pure raw material foundation for subsequent processes, minimizing batch-to-batch performance variations caused by moisture fluctuations.
[0072] Example 3: Based on the above-mentioned deep drying supplement, the absolute pressure of 1-3 kPa in the deep drying in step one above is set to an absolute pressure of 3 kPa, while other contents remain unchanged;
[0073] Under vacuum conditions with an absolute pressure of 3 kPa, the boiling point of water is reduced to approximately 68°C, significantly lower than 100°C under normal pressure. This drying environment efficiently removes most of the free and bound water from biomass feedstocks while effectively preventing thermal damage to the natural microstructure of the feedstocks caused by high temperatures. Although the drying efficiency is slightly lower than under more extreme vacuum conditions, the moisture content can still be stably controlled at a low level (typically below 2.5%), providing a precursor with good structural integrity for subsequent carbonization.
[0074] Control group 1, based on the above-mentioned deep drying supplement, removes the deep drying in step one above, while keeping other contents unchanged.
[0075] Control group 2, based on the above-mentioned deep drying supplement, sets the absolute pressure in the deep drying in step one above from 1-3 kPa to 3.1 kPa, while keeping other contents unchanged.
[0076] Control group 3, based on the above-mentioned deep drying supplement, sets the absolute pressure in the deep drying in step one above from 1-3 kPa to 0.9 kPa, while keeping other contents unchanged.
[0077] Comparison of feasibility under different absolute pressure drying conditions
[0078] Absolute pressure (kPa) Atmospheric pressure 3.1 3 2 1 0.9 Boiling point of water (°C) 100 69 68 60 45.8 44.5 Moisture content (%) after drying >5 >3 ≤2.5 ≤2 ≤1.5 ≤1.4 Impact on plasma process stability Severe damage prevents stable operation High risk: Moisture fluctuations can easily cause process interruptions It is basically feasible (with occasional slight fluctuations that require monitoring). Stability provides a pure and stable environment for plasma. Extreme stability provides the optimal environment for plasma Extremely stable (but with an unbalanced cost-benefit ratio). Impact on material properties Poor performance, first-time efficiency <70%, numerous structural defects Performance critical first-efficiency ~78%, poor batch consistency Performance meets initial efficiency (>80%), sufficient for some applications. Excellent performance and stability with first-time efficacy >85% and good batch consistency. Best performance with an initial efficiency of >88%, top-tier performance It offers the best performance (but there is no significant improvement compared to 1 kPa). Overall evaluation Not recommended Not recommended Economical solution Optimal Balanced Scheme Performance The inferior solution is costly. Not recommended due to extremely low marginal benefits and poor economic efficiency.
[0079] The "Comparison Table of Comprehensive Feasibility for Drying Conditions under Different Absolute Pressures" shows that an absolute pressure range of 1-3 kPa represents the optimal window for the pre-drying process of preparing high-performance hard carbon anode materials using microwave plasma drying. This window successfully balances technical feasibility, cost-effectiveness, and product performance. The 2 kPa condition is considered the best balance point for industrial application, achieving excellent drying results with a moisture content ≤2.0% with moderate equipment requirements. This provides a solid guarantee for the stable operation of subsequent plasma processes and the high initial efficiency (>85%) and long cycle life of the materials. However, deviations from this window, whether from increasing to 3.1 kPa leading to performance sliding towards the critical point, decreasing to 0.9 kPa resulting in a sharp drop in marginal benefits, or complete failure when using atmospheric pressure drying, all lead to significant deterioration in process stability or product performance.
[0080] Furthermore, based on the above step two's requirement of maintaining the electron temperature stably within the 2-3 eV range, the following needs to be added:
[0081] Example 4: The electronic temperature in step two above is kept stable within the range of 2-3 eV, and the absolute pressure is set to 2 eV, while other contents remain unchanged;
[0082] Maintaining an electron temperature of 2 eV is crucial for achieving an efficient and mild carbonization reaction. This energy level is higher than the bond energies of the CH and CO bonds in lignocellulose, allowing high-energy electrons to efficiently break these chemical bonds through collisions, initiating carbonization reactions such as dehydrogenation and deoxygenation. Simultaneously, the energy of 2 eV is far below the threshold that could cause carbon atom sputtering or excessive graphitization, ensuring the selectivity of the reaction and enabling the orderly reconstruction of the carbon framework, laying the foundation for the formation of an ideal hard carbon structure.
[0083] Example 5: The electronic temperature in step two above is kept stable within the range of 2-3 eV, and the absolute pressure is set to 2.5 eV, while keeping other parameters unchanged;
[0084] Stabilizing the electron temperature at 2.5 eV significantly improves the rate and completeness of the carbonization reaction. Compared to 2 eV, the higher electron energy allows high-energy electrons to more efficiently generate a greater number of reactive species, such as excited-state atoms, ions, and free radicals, when colliding with process gas molecules. These highly reactive particles bombard the biomass precursor more violently, ensuring not only the rapid breaking of CH and CO bonds but also contributing to the disintegration of more stable carbon ring structures, thereby accelerating the formation of sp² carbon networks and shortening the residence time required to reach the predetermined degree of carbonization.
[0085] Example 6: The electronic temperature in step two above is kept stable within the range of 2-3 eV, and the absolute pressure is set to 3 eV, while other contents remain unchanged;
[0086] Stabilizing the electron temperature at 3 eV enables the extreme carbonization reaction rate and depth. This energy level is far higher than the bond energy of most chemical bonds in biomass, generating a large number of high-energy electrons and active particles that violently bombard the precursor, not only completely breaking CH and CO bonds but also effectively dismantling the connecting bonds between more stable aromatic ring structures. This results in the rapid release of small molecule gases, making the carbonization process extremely rapid and thorough, and is particularly suitable for processing some precursor raw materials with more stable structures and more difficult to graphitize.
[0087] Compare with Example 4: Delete step two above, leaving all other content unchanged;
[0088] Compare with Example 5: Set the electronic temperature to be stably controlled within the range of 2-3 eV in step two above to an absolute pressure of 3.1 eV, and keep all other settings unchanged.
[0089] Operating at an electron temperature of 3.1 eV significantly exceeds the process optimization window, resulting in substantial damage to the material structure. Excessive electron energy causes high-energy particles in the plasma to exert a powerful physical bombardment effect, initiating a sputtering etching effect on the initially formed carbon framework. This not only disrupts the inherent natural porous template of the biomass precursor, leading to partial micropore collapse and fusion, but may also cause localized disordering of carbon sp² clusters, introducing numerous irreversible defects into the material. Ultimately, this obstructs ion diffusion channels and reduces the reversible capacity of hard carbon materials.
[0090] Compare with Example 6: Set the electronic temperature in step two above to be stably controlled within the range of 2-3 eV, and set the absolute pressure to 1.9 eV.
[0091] Stabilizing the electron temperature at 1.9 eV leads to insufficient kinetics and decreased efficiency in the carbonization reaction. This energy level is slightly below the optimal threshold for efficient breaking of CO bonds (~3.5 eV) and CH bonds (~4 eV), resulting in a weakened impact force between high-energy electrons and active species. This manifests as incomplete bond breaking, a significant slowdown in deoxygenation and dehydrogenation reaction rates, and a need to substantially extend the residence time of the material in the plasma region to achieve the desired degree of carbonization. This reduces overall production efficiency and may leave behind more unstable organic components or heteroatoms due to incomplete reactions, affecting the electrochemical stability of the carbon material.
[0092] Comparison table of different electronic temperature process parameters and material properties
[0093] Electron temperature (eV) - 1.9 2.0 2.5 3.0 3.1 carbonization mechanism External heating Plasma-assisted (insufficient energy) Plasma activation Plasma activation Plasma activation Plasma-assisted (excess energy) Required stay time (min) 120 35 25 15 8 7 Process control difficulty Low Low medium medium High (requires precise control) Extremely high (difficult to control, prone to fluctuations) Interlayer spacing (nm) 0.380 0.395 0.388 0.382 0.378 0.375 Specific surface area (m² / g) 4.5 8.2 4.8 3.5 6.0 9.5 Pore structure evaluation Partial collapse, uneven underdevelopment Ideal (1-10nm) Ideal (1-10nm) Some micropores were damaged Numerous defects and coarsened pores First Coulomb Efficiency (ICE, %) 78 81 86 88 85 80 Reversible capacity (mAh / g) 290 275 315 330 305 285 Cycle retention rate (2000 cycles, %) 85 87 92 93 89 84 Overall evaluation Poor performance and high energy consumption Incomplete reaction, low performance Optimal balance of high performance, high stability, and high cost-effectiveness Optimal performance, high efficiency, top-tier performance, suitable for doping. Highly efficient but risky; performance may degrade. Through the process, structural damage and performance degradation
[0094] As shown in the "Comparison Table of Comprehensive Feasibility of Drying Conditions under Different Absolute Pressures," the optimal process window for preparing high-performance hard carbon anode materials via microwave plasma low-temperature carbonization is within the range of 2-3 eV. Its core value lies in precisely balancing reaction efficiency, structural protection, and process controllability. Specifically, 2.0 eV was identified as the optimal balance point for industrial applications. It allows for efficient carbonization with a residence time of 25 minutes, resulting in materials with ideal pore structure (1-10 nm), suitable interlayer spacing (0.388 nm), and low specific surface area (4.8 m² / g). This also endows the product with excellent electrochemical performance (86% initial coulombic efficiency, 315 mAh / g reversible capacity, and 92% capacity retention after 2000 cycles), perfectly achieving a balance between high performance, high stability, and high cost-effectiveness. The 2.5 eV condition represents peak performance, further reducing reaction time to 15 minutes and achieving top-tier electrochemical performance (88% first-time efficiency, 330 mAh / g capacity). It is particularly suitable for specialty products or doping processes with extreme efficiency requirements, but it demands slightly higher process control. Once the electron temperature deviates from this window, whether it is as low as 1.9 eV leading to insufficient reaction kinetics and poor structural development (interlayer spacing of 0.395 nm, capacity of only 275 mAh / g), or as high as 3.0 eV and above triggering physical bombardment effects, such as an anomalous increase in specific surface area to 6.0-9.5 m² / g and an increase in structural defects, both will lead to a significant degradation in the material's various properties.
[0095] The technical scope of this invention is not limited to the content described above. Those skilled in the art can make various modifications and variations to the above embodiments without departing from the technical concept of this invention, and all such modifications and variations should fall within the protection scope of this invention.
Claims
1. A method for producing a hard carbon anode material, characterized in that, Includes the following steps: S1. The biomass raw material is crushed, graded and deeply dried to obtain a dry powder with a particle size of less than 100μm and a moisture content of less than 2wt%. S2. In a low-pressure inert atmosphere, a working gas is introduced into the reaction chamber, and microwave energy is applied to generate plasma. The dried powder is continuously and uniformly fed into the plasma region for carbonization reaction. The plasma state is monitored in real time by optical emission spectrum, and the electron temperature of the plasma is stably controlled within the range of 2-3 eV by adjusting the microwave power or working gas pressure, while the reaction temperature of the material bed is controlled within 150-200℃. In S2, the plasma state is monitored in real time through optical emission spectroscopy, and the electron temperature of the plasma is stably controlled within the range of 2-3 eV by adjusting the microwave power or working gas pressure. Specifically, the following operations are performed: S21. Install an optical emission spectral probe on the plasma reaction chamber and calibrate the optical emission spectral probe to ensure that it is aligned with the plasma luminescence region so that it can accurately identify and collect the intensity signal of specific wavelength spectral lines, with a focus on monitoring the argon atom spectral line and the second positive band of nitrogen molecules. Argon atom spectral lines: The spectral line at 750.4 nm was selected as the monitoring target; S22. Pre-calibrate the argon atomic spectral line intensity under the current process gas background. Compared with the intensity of the second positive band of nitrogen molecules ratio The corresponding functional relationship curve between the plasma electron temperature and the plasma electron temperature is obtained, and the target intensity ratio range corresponding to the target electron temperature of 2-3 eV is determined from the functional relationship curve, and this range is set as the benchmark for process control. S23. Introduce working gas, adjust the pressure in the reaction chamber to the target value, apply microwave power, minimize reflected power through the three-screw tuner, and successfully ignite and form a stable plasma. S24. The optical emission spectroscopy probe acquires the emission spectrum of the plasma in real time and calculates it in real time. The instantaneous ratio; S25. Compare the real-time ratio with the target ratio range. If the real-time ratio is lower than the lower limit of the target range, increase the microwave power or decrease the reaction chamber pressure appropriately. If the real-time ratio is higher than the upper limit of the target range, decrease the microwave power or increase the reaction chamber pressure appropriately. If the real-time ratio is within the target range, keep the existing parameters unchanged. S26. After executing the parameter adjustment command, return to S24, collect spectral data again and calculate the ratio to form a continuous closed-loop control loop, ensuring that the electron temperature is dynamically stable within the ideal range of 2-3 eV. S3. The carbonized material is subjected to annealing stabilization and passivation treatment to obtain the hard carbon material.
2. The method for producing hard carbon anode material according to claim 1, characterized in that, The working gas in S2 is argon, and the pressure inside the reaction chamber is kept stable in the range of 10-100 Pa.
3. The method for producing hard carbon anode material according to claim 1, characterized in that, The power of the microwave energy is 500-1100W.
4. The method for producing the hard carbon anode material according to claim 1, characterized in that, The electron temperature of the plasma is stably controlled at 2.5 eV.
5. The method for producing hard carbon anode material according to claim 1, characterized in that, In step S2, during the carbonization reaction, a doping source gas, which is ammonia or phosphorus-containing aerosol, is introduced into the reaction chamber to achieve in-situ doping of nitrogen or phosphorus into the hard carbon material.
6. The method for producing the hard carbon anode material according to claim 1, characterized in that, The deep drying described in S1 is carried out in a vacuum environment at a temperature of 80-120°C for no less than 12 hours, and the absolute pressure of the vacuum environment is 0.5-3.5 kPa.
7. The method for producing the hard carbon anode material according to claim 6, characterized in that, The absolute pressure of the vacuum environment is 1-3 kPa.
8. The method for producing hard carbon anode material according to claim 1, characterized in that, The specific conditions for the annealing and stabilization treatment described in S3 are as follows: under an inert atmosphere, the temperature is increased to 300-400℃ at a heating rate of 1-10℃ / min and held for 1-10 minutes.
9. The method for producing the hard carbon anode material according to claim 1, characterized in that, It also includes step S4, which involves air jet milling and classification of the passivated material to select particles with a D50 particle size of 8-15μm as the final hard carbon anode material.
Citation Information
Patent Citations
Method and device for producing carbon material through non-pollution biomass microwave anaerobic carbonization
CN113942996A